Pengorganisasian Kurikulum Merdeka Dalam Mengembangkan Higher Order Thinking Skills (HOTS) Siswa Sekolah Menengah Di Indonesia: Systematic Literature Review - Diyan Firmansyah; Agus Pahrudin; Sri Rahmi (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
The organization of the Merdeka Curriculum has emerged as a significant factor in fostering the development of Higher Order Thinking Skills (HOTS) among secondary school students in Indonesia. This study seeks to analyze and synthesize findings from previous research concerning the organization of the Merdeka Curriculum in enhancing students’ HOTS through a Systematic Literature Review (SLR) approach. The research was conducted based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. Data were collected from various national and international scientific publications issued between 2021 and 2026 that discuss the implementation of the Merdeka Curriculum and the development of HOTS. Despite these positive findings, the implementation of the Merdeka Curriculum still encounters several challenges, such as limited teacher competence in designing HOTS-based learning, insufficient technological infrastructure, and varying levels of school readiness. Consequently, stronger policy support, continuous professional development programs for teachers, and comprehensive improvements in the education system are necessary to ensure that HOTS development through the Merdeka Curriculum can be implemented effectively, consistently, and sustainably.